Elucidating the mechanism behind and investigating the efficacy of Traditional Chinese Medicine and Traditional Tibetan Medicine in combination with standard therapeutics in hepatocellular carcinoma and cholangiocarcinoma in vitro - Suo, Huizhen; Hochnadel, Inga; Petriv, Nataliia; Franke, Raimo; Schmidt, Jennifer; Limanska, Nataliia; Tugai, Alisa; Jedicke, Nils; Broenstrup, Mark; Manns, Michael P.; Yevsa, Tetyana (Frontiers in Pharmacology, 2022)
In this study, we investigated compounds of plant and mushroom origin that belong to Traditional Chinese Medicine (TCM) and to Traditional Tibetan Medicine (TTM): a sandy beige mushroom Trametes robiniophila Murr, commonly known as Huaier/TCM as well as Ershiwuwei Songshi Wan and Qiwei Honghua Shusheng Wan, which both belong to TTM. We aimed to study the efficacy of TTM and TCM in hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) in vitro. TCM and TTM were tested either as a monotherapy, or in combination with standard therapeutics – sorafenib for HCC and gemcitabine for CCA. We also defined a protective mechanism behind the most successful therapeutic combinations. The results demonstrated that TCM and TTM inhibited the proliferation of cancer cells in a time- and dose-dependent manner. The results were compared to classical chemotherapeutics currently used in the clinic: sorafenib for HCC and gemcitabine for CCA. In HCC settings, a combination of Huaier (16 mg/ml) with half of the human plasma concentration of sorafenib as well as Qiwei Honghua Shusheng Wan (1 mg/ml) monotherapy and its combination with half or even quarter dose of the human plasma concentration of sorafenib represented the most efficient treatment, inhibiting the growth of HCC cells more effectively than the standard therapy. The inhibitory mechanism relied on the strong induction of apoptosis. In CCA settings, Ershiwuwei Songshi Wan and Qiwei Honghua Shusheng Wan as monotherapy or in combination with very low doses of gemcitabine inhibited the growth of CCA cells more efficiently than the standard therapy. Importantly, Ershiwuwei Songshi Wan and Qiwei Honghua Shusheng Wan were efficacious with gemcitabine applied at massively reduced concentrations. The protective mechanism in CCA relied on a strong induction of early and late apoptosis. Cellular senescence and necroptosis were not associated with protection against HCC/CCA. Combinations with TCM and TTM therapy allowed reducing the doses of standard chemotherapeutics. The latter is especially important, as both drugs show strong side effects in patients. The reduction of chemotherapeutics and a synergistic effect observed while applying them in combination with TCM and TTM has strong perspectives for the clinic and patients suffering from HCC and CCA.